Internet Technical Development and Applications - Tkacz, Ewaryst.; Kapczynski, Adrian. (Advances in Intelligent and Soft Computing, 2009)
Internet technologies and systems are nowadays the key enablers of digital economy and modern world-wide connected society. This contributed book is a collection of cautiously chosen articles delivered by specialists with significant level of expertise in the domain of Internet technical foundations and its applications. The content of the book is divided into three parts: Internet - technical fundamentals and applications Information management systems Information security in distributed computer systems This book is a reference tool prepared for scientists and other persons involved in designing, implementation and evaluation of internet technologies. Its readers can be found among researchers, teachers and also students of computer science and related disciplines.